Tents, supplies and lumber on beach at Nome, probably between 1899 and 1900 - Warner, Arthur Churchill, 1864-1943 (1899)
Gold was discovered on the Nome beaches in the Summer of 1899. By Spring of 1900, thousands had arrived for the gold rush. One tent in foreground bears a sign for Dr. Rice. Warner 81a Filed in Alaska series.